Monitoring Kontrol Greenhouse untuk Budidaya Tanaman Bunga Krisan dengan LabView - Sukandar Sawidin; Olga Engelin Melo; Tracy Marsela (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
One of the plants that is cultivated in Tomohon City is Chrysanthemum. Nowadays, the cultivation of chrysanthemum in a greenhouse is still using the conventional method where farmers are difficult to manage the process of watering and light, therefore, the efflorescence of chrysanthemum plants is disturbed. Based on that case, a control system is created using a microcontroller Arduino to adjust the temperature, humidity, light, and watering of plants in the greenhouse, and to monitor the system in a PC using Labview and TCP/IP. The results show that the system has been running according to the plan. Based on the temperature control set point, the valve will be